Amino functionalized oligoimides telechelics - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Deokar, Sarika Babasaheb; Mulani, Khudbudin Baban; Ghorpade, Ravindra V.; Bhongale, Sunil Sitaram; et al. (2010)
This invention relates to a process for the preparation of amino functionalized oligoimide telechelics. More particularly it relates to a process for the preparation of soluble oligoimide prepolymers which can be used as matrix resins that can be rapidly cured to form stable polyimides with amino end functionalities. The amino functionalized oligoimide telechelics are suitable for conversion into three dimensional polymeric systems through condensation chemistry such as reaction with oligo epoxies (epoxy-imide resins), polyacids (polyamide imides) and polyhalogenated compounds (poly amine - imides) to form crosslinked structures having enhanced thermal stability and mechanical strength. The polymers prepared by the process of this invention can be used as materials in advanced composites having high temperature stability.

Adsorption induced enzyme denaturation: the role of protein surface in adsorption induced protein denaturation on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymers - Thudi, Lahari; Jasti, Lakshmi Swarnalatha; Swarnalatha, Y.; Fadnavis, Nitin W.; Mulani, Khudbudin Baban; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Colloids and Surfaces B-Biointerfaces, 2012)
The effects of protein size on adsorption and adsorption-induced denaturation of proteins on copolymers of allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) have been studied. Different responses were observed for the amount of protein adsorbed and denatured on the polymer surface for different proteins (trypsin, alchol dehydrogenase from baker's yeast (YADH), glucose dehydrogenase (GDH) from Gluconobacter cerinus, and alkaline phosphates from calf intestinal mucosa (CIAP). Protein adsorption on the copolymer with 25% crosslink density (AGE-25) was dependent not only on the size of the protein but also on the presence of glycoside residues on the protein surface. Adsorption and denaturation of proteins follows the order YADH > trypsin > GDH >> CIAP although the molecular weights of the proteins follow the order YADH > CIAP > GDH > trypsin. The lack of correlation between amount of adsorbed protein and its molecular weight was due to the presence of glycoside residues on CIAP and GDH which protect the enzyme surface from denaturation. Enzyme stabilities in aqueous solutions of 1-cyclohexyl-2-pyrrolidinone (CHP) correlate well with the trend in denaturation by the copolymer, strongly suggesting that hydrophobic interactions play a major role in protein binding and the mechanism of protein denaturation is similar to that for water-miscible organic solvents. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1-Cyclohexyl-2-pyrrolidinone; Adsorption; Alcohol dehydrogenase; Alkaline phosphatase; allyl glycidyl ether; Denaturation; ethylene glycol dimethacrylate; Glucose dehydrogenase; Trypsin

Amino functionalized oligo polyimides with enhanced storage stability - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Mohan, Srinivasulu Reddy Krishna; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Tayal, Rajiv Kumar; Shadbar, Qureshi Mohammed; Chavan, Nayaku; Deokar, Sarika Babasaheb; et al. (WO2012090055A1, 2012)
The invention relates to an improved process for the preparation of amino functionalized oligomeric monomeric reactant type polyimides having higher stability. More particularly it relates to a process for the preparation of soluble imide prepolymers, used as matrix resins that can be rapidly cured with multi-functional moieties such as diepoxy, dicarboxyl, anhydride, diisocyanates to form crosslinked structures having enhanced thermal stability and mechanical strength.

Enzyme immobilization on epoxy supports in reverse micellar media: prevention of enzyme denaturation - Thudi, Lahari; Jasti, Lakshmi Swarnalatha; Swarnalatha, Yalangi; Fadnavis, Nitin W.; Mulani, Khudbudin Baban; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Journal of Molecular Catalysis B-Enzymatic, 2012)
Immobilization of enzymes such as alpha-chymotrypsin (EC 3.4.21.1), yeast alcohol dehydrogenase (YADH) from Saccharomyces cerevisiae (EC 1.1.1.1) and glucose dehydrogenase (GDH) from Gluconobacter cerinus (EC 1.1.1.119) has been carried out. Copolymers of allyl glycidyl ether (AGE) crosslinked with 25% ethylene glycol dimethacrylate (EGDM) (25 mg, dry wt) were contacted with the enzymes solubilized in reverse micellar media (0.5-5 mg/mL)(overall) of sodium bis(2-ethylhexyl) sulfosuccinate (AOT) salt in isooctane, and cetyl trimethylammonium bromide (CTAB) in chloroform-isooctane (50:50, v/v). Although the enzymes are readily denatured (>90%) after adsorption on the copolymer in aqueous buffers, no such adsorption-induced denaturation takes place in reverse micelles. alpha-Chymotrypsin is remarkably stable in AOT reverse micelles when 0.025 M citrate buffer of pH 9.0 containing 2 mM CaCl2 is used in the water pools instead of Tris-HCl buffer of pH 8.5. It was possible to achieve enzyme concentration of 5 mg/mL in 0.3 M AOT at molar ratio of water to surfactant, (W-0), 30 and to obtain alpha-chymotrypsin loading of 20 mg/g of copolymer. The recovered enzyme solution can be reused with a fresh batch of polymer after supplementing the depleted solution. The immobilized enzyme exhibits excellent stability in aqueous buffers at room temperature and can be recycled several times. YADH is stable in both AOT and CTAB reverse micelles while GDH is stable only in CTAB reverse micelles containing 0.05 M Tris-HCI buffer of pH 8.5. Interestingly, the combination of YADH (2.5 mg/g) and GDH (0.5 mg/g) co-immobilized on the copolymer using CTAB-chloroform-isooctane system can be used for regeneration and recycle of NADPH at least 50 times as exemplified by complete reduction of a prochiral ketoester, ethyl 4-phenyl-2,4-dioxobutyrate (10 mM) to ethyl (R)-2-hydroxy-4-phenylbutyrate (HPB ester) using NADPH (0.2 mM). (C) 2011 Elsevier B.V. All rights reserved.
Keywords: allyl glycidyl ether; alpha-Chymotrypsin; ethylene glycol dimethacrylate; Glucose dehydrogenase; Reverse micelles; Yeast alcohol dehydrogenase

Ethyl oligo-silicates with strong acid heterogeneous polymeric catalysts - Bevara, Madhusudana Rao; Bhongale, Sunil Sitaram; Bhosle, Sonali Madhavrao; Chavan, Nayaku; Chelanattukizhakkemadath, Raman Rajan; Deokar, Sarika Babasaheb; Dhoble, Deepa Arun; Dwivedi, Mayank; Ghorpade, Ravindra V.; Harikrishna, Reghunathan; Dhanasekharan, Janakiraman; John, Aruldoss; et al. (WO2012056290 A1, 2012)
The present invention provides a process for the synthesis of ethyl silicate with varying silica concentration, by hydrolysing ethyl silicate in varying water concentration in the presence of sulfonated catalysts having a styrene-divinyl benzene backbone. The present invention further relates to the preparation of beaded crosslinked polymers containing sulfonic acid moieties having an interconnected pore structure and surface area up to 400 m2 /g.

Synthesis and characterization of azoxy based mesogenic diols - Mulani, Khudbudin Baban; Ganjave, Nitin V.; Chavan, Nayaku (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2014)
Azoxy based rigid mesogenic diols have been synthesized using two steps. Phenol/cresol is used as starting material. Synthesized diols are characterized by IR, H-1 and C-13 NMR, and mass spectroscopic methods. Thermal properties have been determined by thermo gravimetric analysis method and crystallinity patterns have been obtained by wide angle X-ray diffiactogram. Substituted phenol (methyl) is used to study the effect of substitution on physical and thermal properties of rigid azoxy mesogenic diol. The detailed characterization of azoxy based rigid diols is reported in this communication, which is highly useful for fundamental and applied research, particularly in liquid crystals and liquid crystalline polymers. The experimental results reveal that phenol based rigid mesogenic diols have high thermal stability and degree of crystallinity than methyl substituted rigid mesogenic diols.
Keywords: Azoxy; degree of crystallinity; diol; mesogen; phenol; thermal stability

Synthesis and characterization of triad based rigid mesogenic diols derived from hydroquinone and 4-hydroxybenzoic acid - Mulani, Khudbudin Baban; Ganjave, Nitin V.; Chavan, Nayaku (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2014)
Triad based rigid mesogenic diols have been synthesized by four step synthesis method using protection-deprotection method. Hydroquinone and 4-hydroxy benzoic acid have been used as starting materials. Synthesized diols have been characterized by IR, H-1 and C-13 NMR, and mass spectroscopic methods. Thermal properties have been determined by thermo gravimetric analysis method and degree of crystallinity have been measured by wide angle X-ray technique. Substituted hydroquinones (methyl and chloro) have been used to study the effect of substitution on physical and thermal properties. Synthesis of rigid mesogenic diol monomer using p-hydroxy benzoic acid and hydroquinone is reported, which is a facile route. Hydrolysis of diacetate derivatives of rigid mesogenic diols is performed in good yields, even though two types of ester groups present in the same moiety, aromatic and aliphatic. The experimental results reveal that hydroquinone based rigid triad mesogenic diol have high thermal stability and degree of crystallinity as compared to methyl-and chloro-substituted rigid triad mesogenic diols.
Keywords: degree of crystallinity; ester hydrolysis; Mesogenic diols; spectral properties; Thermal properties

Thermotropic liquid crystalline polyesters derived from bis-(4-hydroxybenzoyloxy)-2-methyl-1,4-benzene and aliphatic dicarboxylic acid chlorides - Mulani, Khudbudin Baban; Momin, Mohasin Shamshuddin; Ganjave, Nitin V.; Chavan, Nayaku (Bulletin of Materials Science, 2015)
A series of thermotropic liquid crystalline polyesters derived from bis-(4-hydroxybenzoyloxy)-2-methyl-1,4-benzene(BHBOMB) and aliphatic dicarboxylic acid chlorides were investigated. All these polyesters were synthesized by interfacial polycondensation method and characterized by differential scanning calorimetry and wide-angle X-ray diffractometer. These polyesters consist of BHBOMB as a mesogenic diol and aliphatic diacid chlorides were used as flexible spacers. The length of oligomethylene units in polymer was varied from the trimethylene to the dodecamethylene groups. The transition temperatures and thermodynamic properties were studied for all these polymers. All these polyesters were soluble in chlorinated solvents such as chloroform, dichloromethane, dichloroethane, etc. More importantly, all these polyesters exhibited very large mesophase stability.
Keywords: dicarboxylic acid chloride; interfacial polycondensation; Liquid crystalline polyesters; rigid diol; thermotropic